ISLAMISASI DAN INTEGRASI ILMU PENGETAHUAN DALAM PERSPEKTIF SYED MUHAMMAD NAQUIB AL-ATTAS - Muhammad Jamaluddin; Kholili Hasib; M. Ardiansyah (CV. Jendela Gagasan, 2025)
The phenomena of globalization and modernity have had a significant impact on the development of science and education in the Muslim world, particularly through the dominance of a secular paradigm that separates rationality from spirituality. This situation has given rise to an epistemological crisis that has led to the fragmentation of knowledge and the emergence of intellectual and spiritual identity confusion. This study aims to examine the concepts of Islamization and the integration of science from the perspective of Syed Muhammad Naquib al-Attas, highlighting their theoretical and practical implications for Islamic education. The method used is qualitative with a literature study, through the stages of source identification, literature search, selection based on relevance criteria, recording and documentation, to data organization for further analysis. The analysis is carried out descriptively-analytically and critically-comparatively to find patterns of meaning that are in harmony with the Islamic worldview. The results of the study show that the Islamization of science is interpreted as an effort to liberate knowledge from the hegemony of Western secularism, while the integration of science emphasizes the importance of uniting religion, science, and ethics with tawhid as its main foundation. This concept affirms the position of adab as the core of education, while also offering alternatives in curriculum development, policy formulation, and strategies for empowering Muslims in facing the challenges of globalization. From a theoretical perspective, this research enriches the discourse on Islamic epistemology, while in practical terms it presents an applicable framework for education that is more contextual and oriented towards the formation of civilized human beings. Thus, these findings open up new opportunities in contemporary Islamic scientific studies, especially in formulating a holistic and transformative educational paradigm.